2019
DOI: 10.20537/nd190306
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Gradient Flow of a Vertical Vortex Fluid in a Thin Layer

Abstract: A new exact solution to the Navier -Stokes equations is obtained. This solution describes the inhomogeneous isothermal Poiseuille flow of a viscous incompressible fluid in a horizontal infinite layer. In this exact solution of the Navier -Stokes equations, the velocity and pressure fields are the linear forms of two horizontal (longitudinal) coordinates with coefficients depending on the third (transverse) coordinate. The proposed exact solution is two-dimensional in terms of velocity and coordinates. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(40 reference statements)
0
3
0
4
Order By: Relevance
“…Скорость жидкости на верхней границе является параболическим профилем относительно координаты y , описывающим суперпозицию поступательного и вращательного движений. Как было показано в статьях [20][21][22][23][24][26][27][28], задание краевого возмущения приводит к генерации вертикальной закрутки в жидкости и неоднородному распределению касательных напряжений.…”
Section: постановка задачиunclassified
See 3 more Smart Citations
“…Скорость жидкости на верхней границе является параболическим профилем относительно координаты y , описывающим суперпозицию поступательного и вращательного движений. Как было показано в статьях [20][21][22][23][24][26][27][28], задание краевого возмущения приводит к генерации вертикальной закрутки в жидкости и неоднородному распределению касательных напряжений.…”
Section: постановка задачиunclassified
“…Недавно были опубликованы статьи, в которых анонсировались обобщения плоского течения Куэтта [20][21][22][23][24][25][26][27][28]. В работах [20][21][22][23][24][25][26][27][28]…”
Section: Introductionunclassified
See 2 more Smart Citations
“…It was shown that the vertical vorticity component can exist when the fluid does not rotate. Isothermal flows of this kind were studied in [38,39]. When considering thermal factors, it is important not only to study their influence on the velocity field, but also to evaluate the contribution of the velocity field to the stratification of the temperature field.…”
Section: Introductionmentioning
confidence: 99%